Integrating Kolb’s experiential learning theory into nursing education: a four-stage intervention with case analysis, mind maps, reflective journals, and peer simulations for advanced health assessment - Cheng, Jing; Wu, Yingting; Huang, Li; Wu, Yuehong; Guan, Yuxiang (Frontiers in Medicine, 2025)
PurposeThis study evaluates the effectiveness of integrating case-based mind maps and reflective journals within Kolb’s experiential learning framework in advanced nursing education.MethodsAn ex post facto design compared 2023 (control group, n = 46) and 2024 (experimental group, n = 57) cohorts of nursing master’s students. The experimental group received a Kolb-based intervention comprising: case analysis (concrete experience), reflective journals (reflective observation), mind maps (abstract conceptualization), and peer-led simulations (active experimentation). Outcomes were assessed using the Self-Directed Learning Instrument for Nursing Students (SDLINS), Critical Thinking Disposition Inventory (CTDI-CV), and a teaching satisfaction questionnaire.ResultsThe experimental group demonstrated significantly higher final assessment scores (96.54 ± 1.43 vs. 93.07 ± 1.62, p < 0.001), superior self-directed learning abilities (69.09 ± 7.56 vs. 55.63 ± 7.68, p < 0.001), and enhanced critical thinking skills (288.05 ± 12.41 vs. 260.13 ± 12.02, p < 0.001). All subdomains of these measures showed significant improvements (p < 0.05). Teaching satisfaction was markedly higher in the experimental group across all dimensions (p < 0.001), with particular strengths noted in teaching attitude (18.09 ± 2.68 vs. 11.35 ± 2.09) and classroom teaching (23.02 ± 3.59 vs. 17.83 ± 2.70).ConclusionThe systematic implementation of Kolb’s experiential learning cycle through case-based mind mapping and reflective journaling can facilitate the development of master’s nursing students’ competency in clinical advanced health assessment. This pedagogical approach effectively connects theoretical knowledge and clinical practice while fostering students’ critical thinking and self-directed learning skills.